Sustainable Supply Chain Management of Cocoa Beans in Indonesia: A Review - Noer Novijanto; Dyah Ayu Savitri; Setiyono; Gatot Subroto; Herlina (Newinera Publisher, 2022)
This review describes the sustainable supply chain management of cocoa beans in Indonesia. Cocoa beans are produced in some areas in Indonesia such as Central Sulawesi Province, Southeast Sulawesi, South Sulawesi, West Sulawesi, Lampung and other provinces. Indonesian cocoa beans performing special characteristic that is having higher melting point therefore it does not easily melt in higher temperature. So, Indonesian cocoa are commonly used for blending materials. In order to support the strength value of Indonesian cocoa beans, the sustainable supply chain management should also be considered. The sustainable supply chain management of cocoa beans will support the management system prioritizing balance and sustainability so that the business system is maintained. In addition, this will support increased effectiveness, efficiency and competitiveness of Indonesian cocoa beans globally.